Pharmacogenomics of multifactorial diseases: a focus on psoriatic arthritis. (June 2016) - Cascella, Raffaella; Strafella, Claudia; Longo, Giuliana; Maccarone, Mara; Borgiani, Paola; Sangiuolo, Federica; Novelli, Giuseppe; Giardina, Emiliano
This review will outline the current pharmacogenomics knowledge about psoriatic arthritis with a special attention to the perspectives and the challenges for its implementation in the clinical practice. To date, different drugs have been developed to contrast the symptoms and the progression of psoriatic arthritis. However, patients have shown high variability of drug response in relation to their genetic makeup. In this context, the advances made in the knowledge and the potentialities of genome-drugs associations paved the path for the development of a precision medicine. In fact, these associations may be successfully combined with the environment information to provide new strategies able to prevent and improve the disease management as well as to enhance the patients quality of life.